Severe occupational hand eczema, job stress and cumulative sickness absence - Böhm, Dana Katja; Stock Gissendanner, S.; Finkeldey, F.; John, S. M.; Werfel, T.; Diepgen, Thomas L.; Breuer, K. (Occupational medicine, 2014)
AbstractBackground. Stress is known to activate or exacerbate dermatoses, but the relationships between chronic stress, job-related stress and sickness absence
Gesehen am 15.07.2020